Services for Effective Rural Governance A Design Thinking View - Zejda, Vladimír; Jiřinová, Kateřina; Jetmar, Marek, 1976-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2014)
This paper takes a look at the challenges mayors of Czech small towns face in they day-to-day job and presents a comprehensive overview of ways they can be addressed. It then focuses on the non-financial and non-legislative tools of cooperation and external support in particular, which are introduced under a collective name "services for effective rural governance". The thesis then presents on the concept of "service design" and its uses in the public sector. Consequently, this method is used to analyze and propose changes to the currently available services for effective rural governance so that they best serve the small town mayors.
Vedoucí práce: Kateřina Jiřinová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses